Effect of coping strategies on acute stress during the COVID–19 pandemic in Greece - Strongylaki, Nefeli Paraskevi; Pilafas, Georgios; Dermati, Anastasia; Menti, Despina; Lyrakos, Georgios (Health & Research Journal, 2021)
Background: The psychological impact of quarantine, due to the SARS COVID-19 outbreak, was examined with a specific focus on the relationship between 7 coping strategies: (i) active coping, (ii) positive reframing, (iii) acceptance, (iv) use of emotional support, (v) religion, (vi) substance use and (vii) self-blame and acute stress. This study aimed to identify specifically which of those coping strategies could increase or decrease acute stress levels. Method and Material: The data collection took place during the lockdown and was performed using online surveys. The finale sample size reached up to 1154 Greek adults (age M= 40.51). Two adapted and translated scales were used to measure the variables of interest, including: Brief-COPE questionnaire as well as Acute Stress Disorder Scale (ASDS). Results: “Active coping”, “acceptance”, “positive reframing” and “emotional support”, four of the coping strategies examined, that were found to be significantly associated with stress reduction. Meanwhile, “religion”, “self-blame” and “substance use” were not associated with stress reduction. Conclusions: This study initially provides an insight of acute stress and effective coping strategies associated with the quarantine period during the COVID – 19 pandemic in Greece. The outcome of this study equip support for the expected inflation of the mental health issues stemmed from the unusual stressors, and urge clinicians, mental health providers, and public agencies to assemble, in an attempt to make possible the widespread implementation of more effective and beneficial coping strategies.